Psychological Capital: Perkembangannya dalam sepuluh tahun terakhir - Ilham Medal Junjunan; Aditya Eka Putra (LPPM UNIBI, 2020)
Continuous development in the organization plays a very important role in achieving long-term success. In a business world that continues to grow and change rapidly, organizations are required to be able to keep abreast of technological developments, industry trends and market needs. Without efforts to continuously develop and adapt, organizations can be left behind and lose competitiveness. So it can be concluded that organizations that are unable to adapt to change will be left behind in the competition. Therefore, it is very important for companies to improve their individual competence. One way to improve competence in individuals can be done by developing psychological capital in individuals. By developing psychological capital (psycap) in individuals, organizations can create conditions that support their development. Psycap is still very relevant to be discussed. So, the purpose of this systematic literature review is to find out how the theory and findings of psycap have developed in the last ten years. Psycap plays an important role in organizational development, individual health and academic performance. A high psycap tends to indicate higher levels of job involvement, higher job satisfaction, and stronger commitment to the organization. Psycap also acts as a mediator in the relationship between factors such as leadership, organizational justice, and psychological empowerment and desired outcomes. In addition, psycap can also moderate the negative effects of stressors and challenges on boredom at work. It is important for organizations to develop strategies that strengthen individual psycaps, through the development of new products and services, renewal of business processes, and improvement of individual competencies, to achieve long-term success and maintain competitiveness.